Emerging role of physiotherapy in management of crush injury over forearm - Ray, Mansi (International Journal of Advances in Medicine, 2022)
The objective of the case report is to discuss the case of a patient with crush injury over right forearm. A 37 years old male came with complain of pain, swelling, restricted range over affected side, muscle weakness over right forearm, wrist and hand, reduced grip strength on right hand, and difficulties in ADL’S over right-hand following crush injury over right forearm. Treatment involved physical therapy and Electro modalities for the elimination of pain and returning the patient’s full range of motion in the wrist and hand. After range of motion was restored, a home exercise program was initiated. The home exercise program included a return to ADLs and occupational related activity and active, resistive, gripping activities of the hand. After 11/2 month follow up, our patient showed dramatic recovery after appropriate Surgical and physiotherapy management. Physiotherapy plays significant role in the elimination of pain, improving range; muscle strength and hand function and also reduces the risk of stiffness, contracture and deformity in crush injuries.